Analisis dan Evaluasi: Sarana Kepastian Hukum Regulasi: (Dampak Lahirnya Peraturan Perundang-Undangan dan Judicial Review) - Andrian Erickatama; Wicipto Setiadi (Jimly School of Law and Government, 2024)
The Nomenclature of Regulatory is the rules made by the authorities to regulate something. Analysis and evaluation of the law and regulation is juridically recognized with the birth of Law No. 13 of 2022. As might be expected, this authority was born on the basis of needs. As a result, analysis and evaluation should be the main capital in the formation of regulation, be it an amendment or replacement of existing laws and regulations. This research uses a normative method with a qualitative approach. The approach used in this research is a statutory approach and conceptual approach. How is the role of analysis and evaluation in the implementation of the delegation article of the enactment of regulation and how is the concept of analysis and evaluation as in the outcome of Judicial Review. Analysis and evaluation of legislation is an executive review mechanism to determine legal needs, the basis for determining the effectiveness of legislation and as a follow up to judicial review to assure legal certainty. The Ministry of Law c.q BPHN as an institution given by the authority to conduct analysis and evaluation of Regulations must promptly accelerate to maximize the role of analysis and evaluation needed by the Government as the organizer of the Government and the society so that legal certainty will be produced regarding the effectiveness of a law or regulation.